The Effect of the Socio-Scientific Inquiry (SSI) Learning Model on the Comprehension of Ecosystem Concepts by High School Students - Yara Maulina Nasution; Ummi Nur Afinni Dwi Jayanti (Universitas Labuhanbatu, 2024)
Understanding biological concepts is the main target of learning because it relates to the Sustainable Development Goals (SDGs) objectives. However, understanding biological concepts still needs to be solved in Indonesia, one of which is the low understanding of biological concepts in ecosystem material. The purpose of this study is to ascertain how students' comprehension of concepts in ecosystem material is impacted by the Socio Scientific Inquiry (SSI) learning approach. A quasi-experiment with a two-group pre-test-post-test design was used in the research methodology. The sampling technique used was cluster random sampling. The research instrument was an essay with ten concept understanding questions in it. To find the standard deviation, mean, median, and mode of the data, descriptive analysis was employed as the data analysis approach. The independent t-test was used to assess the study's hypothesis, and the normality and homogeneity tests were run for the precondition analysis. The findings of the descriptive analysis show that the average post-test score in the experimental class is 80.50, whereas it is 67.83 in the control class. This discrepancy suggests that the experimental class's average post-test score is higher than that of the control group. T-test result found that the Sig (2-tailed) value was 0.000 < 0.05, which resulted in the acceptance of Ha and the rejection of H0. This suggests that students' conceptual comprehension is impacted by the Socio Scientific Inquiry (SSI) learning model. This study concludes that the Socio Scientific Inquiry (SSI) learning paradigm improves students' conceptual comprehension when compared to standard learning paradigms.